Volume 2: Thermal Management; Data Centers and Energy Efficient Electronic Systems 2013
DOI: 10.1115/ipack2013-73187
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Optimization of Porous Medium Heat Sinks for Energy Efficiency and Minimum Mass

Abstract: Use of microchannel heat sinks for high heat flux applications is substantial for thermal management and it is also critical for scalable power generation. For both applications, the energy efficiency consideration of the pump power is crucial. A number of models have been created that predict the performance as a function of the geometrical parameters, taking into account, the pressure loss over the length and volume constraints. Most of the approaches either involve sophisticated calculations incorporating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In separate studies, the impact of heat sink design on the performance is reported [39] and further potential for a cost effective heat sink for energy systems is theoretically analyzed and reported in Ref. [40]. This extensive study of heat sinks based on porous material could yield the theoretical upper limit of COP of the heat sink itself.…”
Section: Cost Factormentioning
confidence: 98%
“…In separate studies, the impact of heat sink design on the performance is reported [39] and further potential for a cost effective heat sink for energy systems is theoretically analyzed and reported in Ref. [40]. This extensive study of heat sinks based on porous material could yield the theoretical upper limit of COP of the heat sink itself.…”
Section: Cost Factormentioning
confidence: 98%